Enhancement of membrane-type 1-matrix metalloproteinase (MT1-MMP) production and sequential activation of progelatinase A on human squamous carcinoma cells co-cultured with human dermal fibroblasts - Sato, T (Nature Publishing Group, 1999)
Matrix metalloproteinase 2 (MMP-2)/gelatinase A plays an important role in tumour invasion and metastasis. Since MMP-2 is secreted as an inactive form (proMMP-2) from tumour and neighbouring stroma cells, the activation process is necessary to express the enzymic activity for degradation of extracellular matrix components. We herein reported that the activation of proMMP-2 was induced in human squamous carcinoma cells co-cultured with normal human dermal fibroblasts. When A431 cells were co-cultured with human fibroblasts at various cell ratios, 72-kDa proMMP-2 was converted to a 62-kDa active form through the appearance of a 64-kDa intermediate. The activation of proMMP-2 by co-culture was also observed in other carcinoma cell lines, HSC-4 and SAS, but not in normal human keratinocytes. We characterized by in vitro invasion assay that A431 cells in co-culture preferentially invaded through Matrigel and the increased invasive activity was inhibited by exogenously adding tissue inhibitor of metalloproteinases 2. The augmented proMMP-2 activation by co-culture was achieved by the increase in membrane type 1-MMP (MT1-MMP) production along with that of its mRNA level. The predominant appearance of MT1-MMP was immunologically observed in A431 cells, but not human fibroblasts of the co-culture. Furthermore, epidermal growth factor (EGF) enhanced the co-culture-mediated proMMP-2 activation by increasing the production and gene expression of MT1-MMP, and thereby tumour invasive activity was further augmented. These results suggest that the cell–cell contact between carcinoma cells and normal fibroblasts enhances the production of MT1-MMP followed by sequential activation of proMMP-2 on the tumour cell surface, which may be closely implicated in tumour invasion in vivo. © 1999 Cancer Research Campaign